Experimental Rodent Models of Cardiovascular Diseases - Jia, Tian; Wang, Chen; Han, Zhengxi; Wang, Xiaozhi; Ding, Ming; Wang, Quanyi (Frontiers in Cardiovascular Medicine, 2020)
Cardiovascular diseases, as the most common non-communicable disease in the world, cause a high mortality rate today, and bring a serious medical burden to countries worldwide, especially low- and middle-income countries. Experimental rodent models are widely used for cardiovascular diseases researches due to the effective simulation of human cardiovascular diseases, strong reproductive ability, and easy detection. Herein we will summarize the pathological manifestations of common cardiovascular diseases and illustrate the establishment of corresponding experimental rodent models in detail.